2006
DOI: 10.1002/eat.20314
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of purging type disorders: Eating disorder not otherwise specified and bulimia nervosa

Abstract: Objective: In light of recent research indicating the clinical significance of eating disorder not otherwise specifiedpurging only (EDNOS-P), differences between women with lifetime bulimia nervosa purging subtype (BN-P) and EDNOS-P were examined.Method: Three groups of women were examined, a control group (n ¼ 684) and two groups with lifetime eating disorders: BN-P (n ¼ 22), and EDNOS-P (n ¼ 53).Results: Women with lifetime BN-P were significantly more likely to use vomiting than women with EDNOS-P but the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
52
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 29 publications
(36 reference statements)
18
52
0
Order By: Relevance
“…This research replicates a growing body of work, 4,5,7,8,14 which has shown that the group of patients who purge in the absence of objective binge episodes closely resembles those with BN P. The EDNOS purging only patients reported as much psychological disturbance on the EDI and Rosenberg self-esteem inventory as did those with BN P. Although the purging only group reported higher levels of depression than the BN P, both groups had very high scores and at these elevated levels of depression the difference in depression scores is likely not clinically noticeable. As well, previous research 8 suggests that differences between these groups on depression may not be stable.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This research replicates a growing body of work, 4,5,7,8,14 which has shown that the group of patients who purge in the absence of objective binge episodes closely resembles those with BN P. The EDNOS purging only patients reported as much psychological disturbance on the EDI and Rosenberg self-esteem inventory as did those with BN P. Although the purging only group reported higher levels of depression than the BN P, both groups had very high scores and at these elevated levels of depression the difference in depression scores is likely not clinically noticeable. As well, previous research 8 suggests that differences between these groups on depression may not be stable.…”
Section: Resultssupporting
confidence: 82%
“…2 A number of recent articles have focused on identifying subgroups of individuals within the broader EDNOS category. [3][4][5][6][7][8] In general, the small literature suggests that there may be justification to relax the current diagnostic boundaries between full syndrome BN and subsyndromal BN. 3,6,9 In addition, there appears to be a clinically significant subgroup of EDNOS patients with a purging only form of eating disorder-EDNOS P, 4,7,8 who both resemble and exhibit differences from patients with BN purging subtype (BN P).…”
Section: Introductionmentioning
confidence: 99%
“…c This group was included in analyses presented by Wade et al 16 and Wade. 17 associated with greater impulsiveness compared with PD. In a second study, Keel et al 8 replicated similarities in body image disturbance, dietary restraint, and overall eating disorder severity using structured clinical interview and self-report measures.…”
Section: Clinical Significance Of Pdmentioning
confidence: 92%
“…Studies that examined purging solely in the context of AN or BN were not reviewed in detail. A total of 14 articles were identified, [5][6][7][8][9][10][11][12][13][14][15][16][17][18] reflecting 10 separate samples of PD. A challenge in reviewing the literature of a condition which has not been formally named or defined is heterogeneity of names and definitions used for the syndrome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation